Social Impact Bonds: Development Prospects in the Russian Federation - D. G. Mirakyan (Мир новой экономики)
Amid the state budget deficit, there is a problem of financing social projects. In this regard, new sources of extrabudgetary funding for social issues need to be sought. Financial instruments capable of implementing various social programs include social bonds. This study identifies the main characteristics of social impact bonds (SIB): fundamental principles, mechanism of work. The current work describes the practice of implementing social impact projects on education, poverty, ecology, etc., presenting the experience of the USA and several European countries. This study analyses Russia’s present state and prosperities in the development of SIB projects. The research defines the unique catalyst-funds role in processes of impact investment, as well as the suitability of their creation in Russia. The author analyses opportunities and likely risks from social impact projects realization.